Two β-amylase genes, OsBAM2 and OsBAM3, are involved in starch remobilization in rice leaf sheaths. (2nd April 2016) - Hirano, Tatsuya; Higuchi, Takayuki; Hirano, Minako; Sugimura, Yu; Michiyama, Hiroyasu
Abstract: To identify mechanisms of starch degradation in rice leaf sheaths at the post-heading stage, we investigated the function of OsBAM2 and OsBAM3, which encode plastid-targeted active β-amylase isoforms, in starch remobilization in leaf sheaths. The starch content in the second leaf sheaths below the flag leaf (the third leaf sheaths) peaked at the flag leaf emergence stage and gradually decreased until 15 days after heading. The mRNA levels of OsBAM2 and OsBAM3 in the third leaf sheaths increased from the flag leaf emergence stage to the heading stage when the starch content began to decrease. However, these mRNA levels did not always remain high during post-heading. Overexpression of OsBAM2 or OsBAM3 markedly repressed starch accumulation in the third leaf sheaths, showing that OsBAM2 and OsBAM3 function in starch degradation in rice leaf sheaths. In contrast, no significant differences in starch content in the third leaf sheaths were detected between knockdown plants of OsBAM2 or OsBAM3 and non-transgenic wild-type plants. Our results suggest that reduced expression of the individual genes, OsBAM2 or OsBAM3, does not result in excess accumulation of starch in the leaf sheaths, probably because of the complementary function of another gene or the action of other genes encoding starch-degrading .